Integrating UHPLC-MS/MS quantitative analysis and exogenous purine supplementation to elucidate the antidepressant mechanism of Chaigui granules by regulating purine metabolism - Jiajun Chen; Tian Li; Dehua Huang; Wenxia Gong; Junsheng Tian; Xiaoxia Gao; Xuemei Qin; Guanhua Du; Yuzhi Zhou (Journal of Pharmaceutical Analysis, 2023)
Chaigui granules (CG) are a compound composed of six herbal medicines with significant antidepressant effects. However, the antidepressant mechanism of CG remains unclear. In the present study, we attempted to elucidate the antidepressant mechanism of CG by regulating purine metabolism and purinergic signaling. First, the regulatory effect of CG on purine metabolites in the prefrontal cortex (PFC) of chronic unpredictable mild stress (CUMS) rats was analyzed by ultra high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) targeted quantitative analysis. Meanwhile, purinergic receptors (P2X7 receptor (P2X7R), A1 receptor (A1R) and A2A receptor (A2AR)) and signaling pathways (nod-like receptor protein 3 (NLRP3) inflammasome pathway and cyclic adenosine monophosphate (cAMP)-protein kinase A (PKA) pathway) associated with purine metabolism were analyzed by western blotting and enzyme-linked immunosorbent assay (ELISA). Besides, antidepressant mechanism of CG by modulating purine metabolites to activate purinergic receptors and related signaling pathways was dissected by exogenous supplementation of purine metabolites and antagonism of purinergic receptors in vitro. An in vivo study showed that the decrease in xanthine and the increase in four purine nucleosides were closely related to the antidepressant effects of CG. Additionally, purinergic receptors (P2X7R, A1R and A2AR) and related signaling pathways (NLRP3 inflammasome pathway and cAMP-PKA pathway) were also significantly regulated by CG. The results of exogenous supplementation of purine metabolites and antagonism of purinergic receptors showed that excessive accumulation of xanthine led to activation of the P2X7R-NLRP3 inflammasome pathway, and the reduction of adenosine and inosine inhibited the A1R-cAMP-PKA pathway, which was significantly ameliorated by CG. Overall, CG could promote neuroprotection and ultimately play an antidepressant role by inhibiting the xanthine-P2X7R-NLRP3 inflammasome pathway and activating the adenosine/inosine-A1R-cAMP-PKA pathway.